Internet and social media as allies of the extension actions of the Good Practices Project during the Covid-19 Pandemic - Gonçalves dos Santos, Jéssica; Barcelos de Aquino, Maria Clara; Batista de Azevedo, Letícia; de Souza Couto Oliveira, Jhenifer; Freitas Brilhante de São José, Jackline (Guará Journal, 2022)
The health crisis imposed by the COVID-19 pandemic caused changes in universities, which needed to organize themselves to ensure the development of academic activities, such as extension projects. The present work aimed to report the use of the internet and social media as extension strategies develo-ped by the ‘Project Good Manipulation Practices in Food Ser-vices: Assessment and Guidance for the Production of Safe Foods’ during the COVID-19 pandemic. The activities reported were carried out between April 2020 and May 2022. Remote meetings have been conducted to reorganize the proposed activities, such as preparing instructional materials and creating an Instagram profile. The extension team developed these activities. As a result, three materials about food safety and COVID-19 were prepared. In addition, content related to the pro-ject’s theme was shared on Instagram, totaling 91 publications. Materials and the social network had repercussions on the target audience and demonstrated the importance of adapting to extension activities. The importance of using the internet and social networks in extension activities is evident, as they add value to the student’s learning process and give the target au-dience greater access to the extension project.